THE EFFECTIVE ROLE OF DIGITAL TECHNOLOGY IN ARABIC LANGUAGE EDUCATION - Khadidja BENCHAHDA & Fatima ABDERRAHMANE (Ziglôbitha)
Abstract: In response to rapid technological advancements, this research emphasizes the need to modernize traditional teaching methods, particularly in Arabic language education. Technology has become essential in improving education quality and fostering student-teacher interaction. The study explores the impact of technology on Arabic language education by defining "didactics," addressing challenges in traditional education, and comparing traditional curricula with technology-based ones. Additionally, it reviews successful examples of digital tool integration. The findings reveal that technology enhances education quality, increases interaction, provides personalized learning opportunities, and makes the educational process more efficient and flexible by offering innovative resources.